Prospek Pengembangan Ekowisata Berbasis Masyarakat di Desa Wisata Betisrejo Kabupaten Sragen - Na’immah Nur’Aini; IA Joko Suyanto (Jurnal Pariwisata Indonesia, 2017)
Tourism village as one of the tourist destinations seed in Sragen Regency need to apply the concept of CBE (Community Based Ecotourism) so potential for development tourist not only to on economic growth but development in social environmental aspects. Purpose of the research is to know the prospect of the development of assessment CBE with object and tourist attraction, community preparedness and readiness development CBE. Method is surveying, interviews and questionnaires. The assessment development CBE standardization follow draft community based tourism developed by WTO and INDECON. The community assessment of the readiness of the community with the determination of using methods respondent random sampling.The result showed that Tourism Village of Betisrejo has the potential to develope into community based ecotourism on potentials objects and fascination with branding image tourism object. The community as potential show positive result and ready. Potential readiness CBE overall show positive results with the socioeconomic aspect, social aspect culture, the aspect of environmental and the management aspect.